Experimental investigation of sliding wear behaviour of boron carbide and mica reinforced aluminium alloy hybrid metal matrix composites using Box-Behnken design. (2021) - Velavan, K.; Palanikumar, K.; Senthilkumar, N.
Abstract: In this work, wear performance of hybrid aluminium metal matrix composite (AMMC) was studied owing to the influence of mica addition on dry sliding. Technique of Stir casting is used to prepare the hybrid composite with AA6061 as matrix phase, 10% boron carbide (B4 C) as primary reinforcement and varying weight fractions of mica (3%, 4% and 5%). Box-Behnken design of Response surface methodology (RSM) is used to analyze the experiments. Pin-on-Disc (PoD) equipment is used to carry out the work for varying sliding speeds, axial load and mica percentage, at room temperature. Coefficient of Friction (CoF) and Friction Force (FF) was evaluated and optimized using desirability approach of RSM. For CoF, the most significant parameter is rotational speed, and for FF it is axial load. Scanning Electron Microscope (SEM) images of worn surface shows grove formation and roughness running in parallel with the sliding direction and abrasive wear mechanism is observed. Optimum condition arrived are; 3% reinforcement of mica, 695 rpm of rotational speed, 0.5 kgf of axial load and 3 min of sliding time with a CoF of 0.207 and FF of 5.47 N.